Sharing Culture and the Economy in the Internet Age - Aigrain, Philippe (Amsterdam University Press, 2012)
In the past fifteen years, file sharing of digital cultural works between individuals has been at the center of a number of debates on the future of culture itself. To some, sharing constitutes piracy, to be fought against and eradicated. Others see it as unavoidable, and table proposals to compensate for its harmful effects. Meanwhile, little progress has been made towards addressing the real challenges facing culture in a digital world. Sharing starts from a radically different viewpoint, namely that the non-market sharing of digital works is both legitimate and useful. It supports this premise with empirical research, demonstrating that non-market sharing leads to more diversity in the attention given to various works. Taking stock of what we have learned about the cultural economy in recent years, Sharing sets out the conditions necessary for valuable cultural functions to remain sustainable in this context. Our software and datasets can be downloaded from the book site at http://www.sharing-thebook.net. On the same site, the reader can also run our models with adjusted parameters and upload datasets in order to run our algorithms for the study of diversity of attention.